The hidden stairs and the magic carpet ebook - Abbott, Tony (Secrets of Droon, 2015)
A hidden door. A magical staircase. Discover the world of Droon! Eric, Julie, and Neal have just found something magic in Eric's basement. They have discovered a staircase to another world! The world of Droon is amazing - full of magic, flying lizards, and fun, furry creatures. But how will Eric, Julie, and Neal find their way home? Maybe their new friend, Princess Keeah, can help?